Authentic videos in ESP classroom: enhancing Aviation English vocabulary acquisition - Tokar, Yevheniia; Fainman, Inna (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This paper reports on the results of an experimental study which seeks to explore the effects of usingauthentic videos on vocabulary acquisition in ESP classes. The participants of the study were divided into acontrol group and a treatment group, each containing 24 students. Both groups attended Aviation English classes for 12 weeks. While the control group was taught by traditional communicative methods, the treatment group was taught via the same tasks coupled with showing of selected authentic videos of around 10 minutes in length, which were related to air crash investigations. The findings indicate that the students who were shown authentic videos statistically outperformed the control group in the post-test. These results are generally congruent with current theory in the field and we conclude that ESP teachers should use authentic video materials to enhance vocabulary acquisition.